Pengaruh Dukungan Pasangan Tehadap Stres Kerja Pekerja Perseroan Terbatas di Kota Bogor - Adinda Dwi Salsabila; Oktavia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2026)
Job stress is a prevalent psychological issue in Indonesia, significantly impacting employee well-being and organizational effectiveness. While social support is a recognized protective factor, Indonesian research has largely focused on organizational support, leaving spousal support relatively under-examined. Drawing on the Buffering Hypothesis and Conservation of Resources Theory, this study conceptualizes spousal support as a vital personal resource for mitigating work-related stressors. This study examines the effect of spousal support on job stress among employees of Limited Liability Companies in Bogor City, an urban industrial hub with high work demands. Using a quantitative approach, data were collected via purposive sampling from 134 employees across three companies. Spousal support was measured using standardized scales (emotional, instrumental, and informational), while job stress was assessed through dimensions of workload, time pressure, role ambiguity, and psychological strain. Simple linear regression analysis reveals that spousal support has a significant negative effect on job stress with a moderate effect size. These findings suggest that higher perceived spousal support is associated with lower job stress levels. Practically, the results underscore the importance of family dynamics in employee welfare policies and work–life balance programs.